2010
DOI: 10.1097/jto.0b013e3181cee2d4
|View full text |Cite
|
Sign up to set email alerts
|

Second-Line Therapy for Elderly Patients with Non-small Cell Lung Cancer Who Failed Previous Chemotherapy Is as Effective as for Younger Patients

Abstract: There were no differences in the efficacy of salvage chemotherapies and EGFR-TKI therapy, in terms of response rate, control rate, and overall survival, in elderly and nonelderly patients, and the therapies had acceptable toxicities. Age itself should not preclude patients with NSCLC from second-line salvage therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…The incidence rate of NSCLC increases gradually with age, and the median age of patients diagnosed with NSCLC is 71 years [2]. Nevertheless, few trials for the chemotherapy of advanced NSCLC have been performed in elderly patients because of the physiological decline of organ functioning, the exhausted functional reserve and the higher possibility of concomitant diseases [3,4]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence rate of NSCLC increases gradually with age, and the median age of patients diagnosed with NSCLC is 71 years [2]. Nevertheless, few trials for the chemotherapy of advanced NSCLC have been performed in elderly patients because of the physiological decline of organ functioning, the exhausted functional reserve and the higher possibility of concomitant diseases [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…In those patients, salvage therapy has been shown to improve survival compared with the best supportive care alone [6,7]. Although the majority of patients enrolled in a salvage trial were younger, several data for salvage treatment have been reported in elderly patients [3,8,9,10,11]. These studies demonstrated that there were no differences in the efficacy of salvage chemotherapy between elderly and nonelderly patients, and old age itself should not be a contraindication for salvage chemotherapy [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent retrospective review of elderly patients receiving a second line therapy analyzing 293 young patients (age < 70) and 168 patients (> 70) treated with second-line treatment (both chemotherapy and EGFR TKIs) showed no differences in both efficacy and toxicity between the two age group [75] .…”
Section: Efficacymentioning
confidence: 99%